Perancangan Model Pengukuran Kinerja Green Supply Chain Pulp dan Kertas - Hendra Saputra; Prima Fithri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2012)
Green supply chain performance measurement system is required to manage environmental risk, increase competitive and obtain appropriate strategy for company. Performance measurement system in PT RAPP only focus on midstream and downstream operation related with manufacturing processes and supplier. The problem is how to redesign existing performance measurement system for pulp and paper in PT RAPP, so that downstream operation related with distributor can be integrated into green supply chain performance measurement system. Research objective designing conceptual and computer model for green supply chain measurement of pulp and wherein information entire supply chain can be managed well. Conceptual model is designed with involving activities such as stakeholder identification, stakeholder green requirement analysis, green objective identification, and KPI weighting. Supply chain operations reference (SCOR) metric is applied to identify key performance indicator (KPI). KPI weighting is determined by AHP method. Computer application is designed by combining database, mathematical formulation, and user interface. it is designed to implement conceptual model. Research result is consisting of two levels with fifteen objectives and twenty seven KPI’s. Proposed application has capability to support decision maker in calculating partial and total performance measure each period. It is designed specifically with quantitative measure to support operational decision making related with environmental aspect.Keywords: Green, supply chain, SCOR, performance measure